Delivery to Macrophages of Interleukin 3 Loaded in Mouse Erythrocytes. Issue 5 (October 2000) - Olmos, Gemma; Lotero, L. Alfredo; Tejedor, M. Cristina; Diez, José C.
Abstract : Mouse carrier erythrocytes containing 125 I-interleukin 3 have been prepared and treated with band 3 crosslinking reagents. The incorporation of interleukin 3 by hypotonic treatment into mouse erythrocytes reached levels of about 15% of the interleukin 3 added to the medium being predominantly present in the cytosolic fraction (73%). Uptake fell to about 7.4% when using the same conditions but omitting hypotonic shock. The interaction of band 3 crosslinked interleukin 3 loaded erythrocytes with macrophages was also studied. A high level of incorporation of interleukin 3 into macrophages was observed either from band 3 crosslinked, interleukin 3-loaded erythrocytes or from interleukin 3 loaded erythrocytes. The observations encourage the view that the system may be able to deliver and target cytokines and other growth factors to macrophages.